USE OF ASSETS FROM A MAQASID SHARIA PERSPECTIVE - Khusnudin, Khusnudin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Wealth has an important position for humans to fulfill various needs which are primary (dharuriyat), secondary (hajiyyat), and tertiary (takhsiniyat).  Various views of ulama place the order of protection of religion, soul, reason, lineage, honor, property, state and security in maqasid sharia.  How to prove the use of assets based on a priority scale based on maqasid sharia is an interesting study.  This qualitative research with a normative approach uses grounded theory in analyzing al-Quran verses related to wealth.  The research results prove that the verses of the Quran command the use of wealth to protect religion, soul, reason, lineage, honor, property, state and security.  The findings of this research strengthen the opinion of the ulama in placing priority needs based on maqasid sharia